2013
DOI: 10.3109/02699052.2013.766929
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after traumatic brain injury: Cohort comparison and economic evaluation

Abstract: More TBI-VR participants returned to work than UC. People with moderate/severe TBI benefitted most. This positive trend was achieved without greatly increased health costs, suggesting cost-effectiveness. This study justifies the need for and can inform a definitive Randomized Controlled Trial (RCT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 46 publications
2
70
1
Order By: Relevance
“…Similar to other authors, we found a tendency for less frequent health care use among patients receiving multidisciplinary treatment [37,40]. This finding could be by chance, but the use of other health care services by patients receiving multidisciplinary treatment must be investigated in other studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to other authors, we found a tendency for less frequent health care use among patients receiving multidisciplinary treatment [37,40]. This finding could be by chance, but the use of other health care services by patients receiving multidisciplinary treatment must be investigated in other studies.…”
Section: Discussionsupporting
confidence: 90%
“…Several authors have suggested that a structured RTW protocol that includes work visits might be beneficial in determining the gap between the patients' capabilities and their work requirements [35,36]. By conducting early standardised visits to the workplace to optimise RTW and by focusing on a gradual exposure to activities upon RTW, as recommended by Radford et al, we assume that RTW would improve [37]. Finally, it is recommended that early vocational rehabilitation be integrated into the early rehabilitation process [35,38].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from 2 Level I studies [45,46] and 2 Level II studies [47,48] reported on the benefit of cognitive interventions to accelerate RTW. In these studies, cognitive interventions were focused on improving memory, post-concussive symptoms, and neuropsychological functioning.…”
Section: Cognitive Rehabilitation Facilitate Return To Work Post Traumentioning
confidence: 99%
“…33 However, the point at which connectivity profiles are stabilized has yet to be identified, and it is plausible that connectivity alterations evident early after injury might endure beyond a critical early window of clinical recovery, typically regarded as the first year postinjury. [34][35][36][37] In the present investigation, we probed longitudinal connectivity changes in a subset of individuals from our TBI group, comparing connectivity profiles derived from rs-fMRI in the subacute phase (approximately 3 months postinjury) to those in the chronic phase. Our aim was to outline the developmental trajectory of any identified changes between the TBI and HC groups, as well as to examine whether functional connectivity changes during the chronic phase are gradually evolving phenomena or if they are relatively more immediate effects of brain injury.…”
mentioning
confidence: 99%